Basil's war ebook A wwii spy thriller. - Hunter, Stephen (2021)
A British spy goes behind enemy lines to crack a secret code in this "highly entertaining World War II espionage thriller" (Seattle Times). Basil St. Florian is an accomplished agent in the British Army, tasked with dozens of dangerous missions for crown and country across the globe. But his current mission, going undercover in Nazi-occupied France during World War II, might be his toughest assignment yet. He will be searching for an ecclesiastic manuscript that doesn't officially exist, one that genius professor Alan Turing believes may hold the key to a code that could prevent the death of millions and possibly even end the war. St. Florian isn't the classic British special agent with a stiff upper lip—he is a swashbuckling, whisky-drinking cynic and thrill-seeker who resents having to leave Vivien Leigh's bed to set out on his crucial mission. Despite these proclivities, though, Basil's Army superiors know he's the best man for the job, carrying out his espionage with enough charm and quick wit to make any of his subjects lower their guards. Action-packed and bursting with WWII-era intrigue (much of which has basis in fact), Basil's War is a classic espionage thriller from Pulitzer Prize-winning critic, essayist, and bestselling novelist Stephen Hunter.